The Effectiveness of the CORE Learning Model Assisted by Interactive E-Modules in Improving Vocational Students’ Critical Thinking Skills - Herningtyas, Salwa; Christian Arief Jaya; Niam Wahzudik (Academia Publication, 2026)
The CORE learning model (Connecting, Organizing, Reflecting, and Extending) is an instructional approach that emphasizes active student engagement in connecting knowledge, organizing information, reflecting on understanding, and extending the application of concepts to real-life situations. This study integrated the CORE model with an interactive e-module to enhance the critical thinking skills of vocational students majoring in Office Management. The research employed a one-group pretest–posttest design involving a saturated sample of 36 tenth-grade students at SMK Hidayah Semarang. Data were collected through pretest and posttest instruments and were analyzed using a paired-sample t-test. The results indicated that the mean score increased from 58.78 (moderate category) to 72.56 (good category). Furthermore, the paired-sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between the pretest and posttest scores. Therefore, the CORE learning model assisted by an interactive e-module was proven to be effective in improving students’ critical thinking skills in the Digital Document subject. Practically, these findings imply that teachers may adopt the CORE model integrated with interactive e-modules as an alternative instructional strategy to promote active learning and foster higher-order thinking skills in vocational education.